Knowledge and scientific and religious belief - Weingartner, Paul (Philosophische Analyse ;, 2018)
The present book is a book on epistemology with the special and new focus on the relation of different types of knowledge and a differentiated comparison to both scientific and religious belief. The present book distinguishes seven types of knowledge and compares them with both scientific and religious belief. The ususal view is that scientific and religious belief have nothing or not much in common. Although there are important differences, in contradistinction to this widespread view it is shown that there are also many similarities between them. There are similarities concerning the reasons for belief, with respect to the action of believing, concerning a similar voluntary component, or even concerning properties of the content of belief. A detailed discussion of many types of knowledge and a differentiated comparison to scientific and religious belief is an important new contribution to the scientific literature in epistemology.